Studi Kelayakan Sarana dan Prasarana Perumahan Nasional (PERUMNAS) IV Padang Bulan - Gilberd Pattiruhu; Deasy Widyastomo; Sudiro Sudiro (Fakultas Teknik Universitas Cenderawasih, 2026)
Based on the current existing conditions, Perumnas IV frequently experiences challenges in both the maintenance of its facilities and infrastructure and the perception of its residents. This study aims to: 1) Determine the morphology and typology of the Perumnas IV Padang Bulan area, 2) Determine the level of feasibility of the infrastructure based on SNI 03-1733-2004, and 3) Determine public perception of the infrastructure based on existing conditions and research analysis results. The research method used by the author in this study is a mixed method using an Explanatory Sequential Design approach and a comparative approach. The difference in feasibility percentages between SNI and public perceptions explains that residents have become accustomed to living with the existing facilities and infrastructure, so that the suitability between existing conditions and applicable technical requirements is not a problem in daily life.